Constructing Biomass‐Based Ultrahigh‐Rate Performance SnOy@C/SiOx Anode for LIBs via Disproportionation Effect. Issue 1 (11th November 2022) - Zhang, Ning; Liu, Kun; Zhang, Haibai; Wang, Xiaofei; Zhou, Yuhao; He, Wenxiu; Cui, Jinlong; Sun, Juncai
Abstract: To break the stereotype that silica can only be reduced via a magnesiothermic and aluminothermic method at low‐temperature condition, the novel strategy for converting silica to SiO x using disproportionation effect of SnO generated via low‐temperature pyrolysis coreduction reaction between SnO2 and rice husk is proposed, without any raw materials waste and environmental hazards. After the low‐temperature pyrolysis reaction, SnO y @C/SiO x composites with unique structure (Sn/SnO2 dispersed on the surface and within pores of biochar as well as SiO x residing in the interior) are obtained due to the exclusive biological properties of rice husk. Such unique structural features render SnO y @C/SiO x composites with an excellent talent for repairing the damaged structure and the highly electrochemical storage ability (530.8 mAh g −1 at 10 A g −1 after 7500 cycles). Furthermore, assembled LiFePO4 ||SnO y ‐50@C/SiO x full cell displays a high discharge capacity of 463.7 mAh g −1 after 100 cycles at 0.2 A g −1 . The Li + transport mechanism is revealed by density functional theory calculations. This work provides references and ideas for green, efficient, and high‐value to reduce SiO2, especially in biomass, which also avoids the waste of raw materials in the production process, and becomes an essential step in sustainable development. Abstract : The stragegy of conversting silica to SiO x via disproportionation effect of SnO is proposed for the first time. The reaction mechanism is revealed and verified by physical characterization. Furthermore, synergism between SnO y and C/SiO x endows conversted composite with excellent electrochemical perfomance. SnO y @C/SiO x can maintain the reversible capacity at ≈540 mAh g −1 under 10 A g −1 after 7500 cycles.